The Influence of Non-Cash Payments on Inflation in Indonesia from 2013 to 2021 - Nala Syifa Dewanti; Wau, Taosige; Putri, Fidela Sintika Amara; Rifa’i, M. Adriansyah; Lubis, Syauqi Ghufran; Jannah, Lulu Lu’luatul (Department of Islamic Economics, Faculty of Islamic Economics and Business, Universitas Islam Negeri Sunan Kalijaga, 2024)
The development of technological advances has led to innovations in the financial sector, namely cash and non-cash payment systems. Among of non-cash payment systems are payments based on ATM/debit cards, credit cards, and various types of electronic money. Moreover, this cause reducing the demand for cash in a country. This study aims to analyze how cashless payments affect inflation rates in the period 2013 to 2021. This research is a quantitative study, the type of data used in this research is secondary data in the form of quarterly time series data sourced from Bank of Indonesia, and Central Bureau of Statistics with a span of 2013-2021. The results using the time series model and OLS (Ordinary Least Square) technique show that electronic money transactions and the BI Rate have a significant effect on inflation in Indonesia. Meanwhile, the transactions based on ATM/debit cards doesn’t have significant effect on inflation in Indonesia.